Systematic review of human gut resistome studies revealed variable definitions and approaches - Jeffery Ho; Yun Kit Yeoh; Nilakshi Barua; Zigui Chen; Grace Lui; Sunny H Wong; Xiao Yang; Martin CW Chan; Paul KS Chan; Peter M Hawkey; Margaret Ip (Gut Microbes, 2020)
In this review, we highlight the variations of gut resistome studies, which may preclude comparisons and translational interpretations. Of 22 included studies, a range of 12 to 2000 antibiotic resistance (AR) genes were profiled. Overall, studies defined a healthy gut resistome as subjects who had not taken antibiotics in the last three to 12 months prior to sampling. In studies with de novo assembly, AR genes were identified based on variable nucleotide or amino acid sequence similarities. Different marker genes were used for defining resistance to a given antibiotic class. Validation of phenotypic resistance in the laboratory is frequently lacking. Cryptic resistance, collateral sensitivity and the interaction with repressors or promotors were not investigated. International consensus is needed for selecting marker genes to define resistance to a given antibiotic class in addition to uniformity in phenotypic validation and bioinformatics pipelines.